MiniCarb: a passive, occultation-viewing, 6U CubeSat for observations of CO2, CH4, and H2O. (19th November 2021) - Wilson, Emily L; Riot, Vincent J; DiGregorio, A J; Ramu, Guru; Cleveland, Paul; Simms, Lance M; Carter, Darrell; Bruner, Bill; Young, Jennifer; Villanueva, Geronimo
Abstract: We present the final design, environmental testing, and launch history of MiniCarb, a 6U CubeSat developed through a partnership between NASA Goddard Space Flight Center and Lawrence Livermore National Laboratory. MiniCarb's science payload, developed at Goddard, was an occultation-viewing, passive laser heterodyne radiometer for observing methane, carbon dioxide, and water vapor in Earth's atmosphere at ∼1.6 µm s −1 . MiniCarb's satellite, developed at Livermore, implemented their CubeSat Next Generation Bus plug-and-play architecture to produce a modular platform that could be tailored to a range of science payloads. Following the launch on 5 December 2019, MiniCarb traveled to the International Space Station and was set into orbit on 1 February 2020 via Northrop Grumman's Cygnus capsule which deployed MiniCarb with tipoff rotation of about 20° s −1 (significantly higher than the typical rate of 3° s −1 from prior CubeSats), from which the attitude control system was unable to recover resulting in a loss of power. In spite of this early failure, MiniCarb had many successes including rigorous environmental testing, successful deployment of its solar panels, and a successful test of the radio and communication through the Iridium network. This prior work and enticing cost (approximately 2 M for the satellite and 250 K for the payload) makes MiniCarb an ideal candidate for a low-cost and rapid rebuild as a single orbiter or constellation to globally observe key greenhouse gases.